FENOMENA PASANGAN TUNGGAL DAN “KOTAK/KOLOM KOSONG” PADA PILKADA KOTA TANGERANG - Bambang Kurniawan, S,Sos., M.Si.; Wawanudin S.IP., M.Si (Jurnal MoZaiK, 2019)
The 2018 Tangerang City Election contest was attended by only incumbent partner Arief R. Wismansyah-Sachrudin. This has become a new phenomenon for the citizens of Tangerang to choose between incumbent Paslon or empty boxes / columns. The purpose of this study was to find out public opinion about the single pair elections in Tangerang City in 2018; 1) knew public opinion about the polity of the incumbent Arief R. Wismansyah – Sachrudin. 2) find out public opinion the performance of Arief R Wismansyah – Sachrudin. 3) knew the level of knowledge of the Tangerang City community about Empty Boxes/ Columns in the Tangerang City election 4) knew the public opinion about the implications if the Empty Boxes/ Columns are more voters 5) knew the level of community participation to come to the polling stations in the Tangerang City election. The analysis that used descriptive analysis. The results of the research have shown that the incumbent paslon is quite popular, the majority of respondents are satisfied with the incumbent paslon performance, the majority were not aware of the existence of empty box/ column pairs and do not knew the implications if empty boxes /columns are chosen/ won.